Influence of Modern Technology on the Teaching and Learning of Business Education Courses in Universities in Edo and Delta States - Iyamu, Ewemade; Chiedu, Augustina Ndidi (NIU Journal of Humanities; Vol 5 No 2 (2020): KIU Journal of Humanities, Vol. 5 No. 2, June 2020, 2020)
The study assessed the influence of modern technology on the teaching and learning of business education courses in universities in Edo and Delta States. Two research questions were raised to guide the study and two null hypotheses were tested at 0.05 level of significance for the study. The sample of the study was 226 final year students and 17 business educators out of the final year 539 students and 17 business educators in Delta State University and Ambrose Alli University using simple proportionate sampling technique. The survey research design was used for this study. The instrument used was validated by three experts. Chronbach Alpha method was used to compute reliability of the instrument which yielded a correlation coefficient of 0.87. Questionnaire was the instrument used for data collection. Data collected were analyzed using descriptive statistics. The t-test was used to test the hypotheses. From the results of the analysis, it was discovered that modern technology such as interactive television and multimedia projector highly influences the teaching and learning of business education courses. Business educators did not differ significantly on modern technology influence with respect to male & female business educators. Consequently, it was recommended that institutions should encourage training and retraining of business educators on the use of these modern technologies. Government at all levels should increase budgetary spending on education especially on procurement of modern/ICT related facilities. Furthermore, non-government organizations should provide both hardware and software of modern technology for adequate utilization.